Presacral epidermoid cyst in a pediatric patient - Lilly Gu; Cara L. Berkowitz; John D. Stratigis; Lee K. Collins; Maria Mostyka; Nitsana A. Spigland (Elsevier, 2021)
Epidermoid cysts are benign cysts of ectodermal origin that are most commonly found on the face, trunk, and neck but have been infrequently described in the presacral region. Presacral epidermoid cysts are most commonly seen in middle-aged women and to our knowledge, only two previous cases have been reported in the pediatric population. In this case report, we present the case of a pediatric patient who underwent a total mass excision with formal coccygectomy for a presacral epidermoid cyst. We describe the differential diagnosis for a presacral mass in a pediatric patient and the clinical, radiographic, and histologic work up involved in obtaining the correct diagnosis. Finally, we discuss the surgical treatment options to remove the mass and to decrease the risk of local recurrence, infection, and other serious complications.